Dakwah Virtual Kadam Sidik Dalam Perspektif Don Ihde: Analisis Mediasi Teknologi Dalam Transformasi Pesan Islam - Aniyq, Meliy Amaliyyah; Wawaysadhya (Jurnal Dakwah Tabligh, 2025)
The development of technology today is increasingly massive. However, this website shows that society has not been able to use da'wah as a guideline to face a change. So in this study the author examines the da'wah kadam sidik regarding technology in the transformation of Islamic messages. Therefore, technology is very much needed for da'wah media. This study discusses the role of technology in the transformation of Islamic messages from Don Ihde's perspective in the Kadam Sidik account. With the aim of providing information about the use of social media as a means to share Islamic messages. In today's modern era, da'wah is expected to handle various increasingly complex problems. Da'wah is an activity that has a goal to invite society towards goodness in the teachings of Islam. Therefore, as humans, we must be able to have awareness first to carry out an activity. Through several ways such as things that encourage humans to be more active in producing goodness including in da'wah activities. An influencer named Kadam Sidik He is a preacher who teaches the book Arba'in Nawawi on his YouTube account with the channel name Mata Naqra, through this platform he can connect with his fans from various circles, such as men and women, with his expertise in providing knowledge about the Hadith of the Prophet contained in the book Arba'in Nawawi. This study uses a qualitative literature study method.